(untitled) (International Journal of Engineering and Computer Science, 2017)
Routing protocols for mobile ad-hoc networks can be broadly classified as position-based (geographic) and topology-based. Geographic routing uses location information of nodes to route messages. Geographic routing protocols use greedy forwarding under which a node forwards a packet to a next node which is closer to the destination than itself; In this paper, we present a geographic Routing protocol, wireless senor networks, position based routing protocol and hybrid routing protocols presented in the literature recently. In which distance vector performs to study include: the distance vector combines greedy perimeter stateless protocol and ad hoc on-demand vector routing protocol. Greedy perimeter stateless routing in wireless sensor network is the routing protocol for mobile adhoc network